Clinico-demographic Characteristics of Colorectal Carcinoma in Bangladeshi Patients - Raza, AKM Maruf; Kamal, Mohammed; Begum, Ferdousy; Yusuf, Md. Abdullah; Mohammad, Din; Begum, Mahbuba; Talukder, Abdur Rabban (Journal of Current and Advance Medical Research, 2016)
Background: Colorectal carcinoma is one of the most common human malignancies worldwide. Objectives: The purpose of the present study was to see the clinico-demographic Characteristics of colorectal carcinoma. Methodology: This cross sectional study was carried out in the Department of Pathology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of November 2009 to July 2010. Patients with colorectal carcinoma from all ages and both sexes were included in the study. Detailed clinical information was obtained by taking history from patient's attendants statement. Fresh unfixed specimens were obtained after surgical resection. Result: A total of 50 cases of colorectal adenocarcinoma from all ages and both sexes were included in the study. The mean age of the 50 cases was 47±14.8 years. Per rectal bleeding was the most common clinical presentation of colorectal carcinoma which was 20(40.0%) cases followed by abdominal pain, altered bowel habit, generalized weakness, anorexia and pallor and p/r bleeding and abdominal pain which were 8(16.0%) cases, 7(14.0%) cases, 6(12.0%) cases and 6(12.0%) cases respectively. Conclusion: In conclusion middle age male patients are the most vulnerable for colorectal carcinoma with common presenting features of per rectal bleeding, abdominal pain and altered bowel habit. Journal of Current and Advance Medical Research 2016;3(1):22-25